2003
DOI: 10.2475/ajs.303.7.622
|View full text |Cite
|
Sign up to set email alerts
|

The Saghand Region, Central Iran: U-Pb geochronology, petrogenesis and implications for Gondwana Tectonics

Abstract: The Saghand area of East-Central Iran exposes rocks that comprise the substratum of the Central Iranian continental terrane, as part of the larger Alpine-Himalayan orogenic system. Our new U-Pb ages and geochemical data from the magmatic, metamorphic and siliciclastic rocks of the Saghand area unravel three main episodes of orogenic activity in the latest Neoproterozoic-Early Cambrian, the Late Triassic, and the Eocene. Geologic events in the oldest episode include in chronological order, low-to medium-grade m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
265
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(289 citation statements)
references
References 50 publications
20
265
1
Order By: Relevance
“…There is therefore reliable evidence of crustal extension between 720-640 Ma, followed by widespread but slow subsidence unaffected by tectonics from 640 to 547 Ma, which is best explained by a model of continental stretching. 525 Ma (Ramezani and Tucker, 2003) suggests subduction of proto-Tethyan crust beyond the continental margin, which converted the Oman and UAE regions into a retro-arc setting on the NE Arabian margin. Thick evaporites and black shales were deposited in a number of 'salt' basins while structural highs focussed carbonate deposition.…”
Section: Arabian Basement Architecturementioning
confidence: 99%
“…There is therefore reliable evidence of crustal extension between 720-640 Ma, followed by widespread but slow subsidence unaffected by tectonics from 640 to 547 Ma, which is best explained by a model of continental stretching. 525 Ma (Ramezani and Tucker, 2003) suggests subduction of proto-Tethyan crust beyond the continental margin, which converted the Oman and UAE regions into a retro-arc setting on the NE Arabian margin. Thick evaporites and black shales were deposited in a number of 'salt' basins while structural highs focussed carbonate deposition.…”
Section: Arabian Basement Architecturementioning
confidence: 99%
“…Although the block was originally thought to have formed during the Pan-African intra-continental extension [50][51][52], it has recently been redefined as a magmatic arc ( Fig. 1) developed along the Proto-Tethyan margin of the Gondwanan supercontinent [45,[53][54][55]. Some authors have reported geological features, predominantly bimodal alkaline volcanism, suggestive of an extensional back-arc regime in the eastern portion of the area [47,48,56].…”
Section: Regional Geologymentioning
confidence: 99%
“…The Bafq district, in which the Kushk deposit occurs, is located within the central part of the Kashmar-Kerman Tectonic Zone [45], also known as the Posht-e-Badam Block [46], of the Central Iranian Zone (CIZ: Fig. 1).…”
Section: Regional Geologymentioning
confidence: 99%
“…In the Kashmar-Kerman Terrane to the west, a 52-Ma high-grade metamorphic gneissic and migmatitic complex is intruded by large late-to post-kinematic calc-alkaline dioritegranite plutons and aplitic dikes of early Eocene age (47-44 Ma; Ramezani and Tucker, 2003). The metamorphic complex is largely the product of anatexis followed by exhumation associated with extensional cordilleran metamorphic core complex formation (Verdel and others, 2007).…”
Section: East-central Iranmentioning
confidence: 99%